PEMBUATAN TREKER RODA BELAKANG DAN LENGAN AYUN SEPEDA MOTOR MATIC DENGAN MEMANFAATKAN DONGKRAK HIDROLIK UNTUK MENINGKATKAN EFEKTIVITAS PEKERJAAN - Rifdarmon Rifdarmon; M. Nasir; Safrijal Safrijal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study discusses the design of the rear wheel treker and swing arm of an automatic motorcycle using a hydraulic jack. Where this tool is made in the form of a Service Special Tool (SST) to remove the rear wheel on an automatic motorcycle. This tool is used to make it easier to remove the rear wheel of an automatic motorbike. This research is the development of previous research. This research was conducted using the research and development method using the 4-D model. The object of this research is an automatic motorcycle. This research was conducted at PT. Great Tower Jl. Veteran No.30 Purus Village, West Padang District. Based on the results of research conducted in several tests using a wheeled (hydraulic) treker in 3 tests, the average time (seconds) was 181.3. When compared with the manual, the ratio of tools made (hydraulic wheel trackers) is 85.8%, while the results of research conducted using wheel trackers (mechanics) in 3 tests obtained an average time (seconds) of 270. When compared with the manual, it has tool ratio (mechanical wheel tracker) 78.9%. From the results obtained, it can be said that the tool made (hydraulic wheel tracker) is 85.8% better than the wheel tracker (mechanical).Keywords Wheel Trek, Rear Wheel and Matic Motorcycle